Comparative evaluation of physiological and molecular responses of blackcurrant varieties to powdery mildew infection - Li, Weihua; Qin, Dong; Ma, Ruiqun; Li, Shuxian; Wang, Lin (Frontiers in Plant Science, 2024)
The black currant (Ribes nigrum L.), a member of the Saxifragaceae family’s Ribes genus, has gained consumer and grower acceptance due to its high nutritional value and economic potential. However, powdery mildew, the primary leaf disease affecting black currants, significantly impacts growers and the industry. Developing varieties highly resistant to powdery mildew is currently considered the most scientifically sound solution. However, the black currant’s physiological and disease resistance mechanisms post-infection by powdery mildew remain understudied, thereby impeding further breeding efforts. Therefore, this study aimed to elucidate the pathogenesis of powdery mildew in various susceptible varieties, post-infection physiological changes, and molecular mechanisms related to powdery mildew. This was achieved through phenotypic observation, physiological data analysis, transcriptomic analysis, and qRT-PCR-mediated gene expression analysis.